BYZANTIUM ASCRIBED AS THE "OTHER" IN PRIMARY SCHOOL HISTORY TEXTBOOKS IN LATE PERIOD OF OTTOMAN EMPIRE. - ÇAM, İrfan Davut; MARTAL, Abdullah (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2019)
The purpose of this study is to show in which contexts the Byzantium Empire is handled in primary school history textbooks in late period of Ottoman Empire, which kind of negative ascriptions it was targeted with, or how it was ascribed as the "other". Unravelling significant findings regarding the image of Byzantium in late period of Ottoman Empire when important transformations occurred in regard of identity construction, this study also endeavours to cast a light on the meanings and missions ascribed to the concept of "us". Designed as a qualitative research towards this purpose, the primary material of the study consists of history textbooks prepared for use in primary schools of the period in question. 15 of these books were chosen. Criteria for this selection included the books in question being prepared in accord with the curriculum in force at the time as well as being approved by the Ministry of Education. Document analysis method was employed to collect data related to the subject of the study from these textbooks. Collected data were analysed with the content analysis technique. According to the results construed from these data the Byzantium Empire was not a subject of history textbooks in all its aspects. It was brought under attention in the context of Islam and especially in the context of Turkish history, but therein it was attributed with negative qualities in various ways and ascribed as the "other".